2013
DOI: 10.1074/jbc.m112.430264
|View full text |Cite
|
Sign up to set email alerts
|

The α-Helical Structure of Prodomains Promotes Translocation of Intrinsically Disordered Neuropeptide Hormones into the Endoplasmic Reticulum

Abstract: Background: Intrinsically disordered neuropeptide hormones are synthesized as larger precursors with an ␣-helical prodomain. Results:The prodomain promotes productive import of the hormone domain into the endoplasmic reticulum (ER) by its propensity to adopt an ␣-helical structure. Conclusion: Impaired ER import of intrinsically disordered proteins can be restored by ␣-helical prodomains. Significance: Secondary structure of the nascent chain can regulate translocation into the ER.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Proglucagon is a unique prohormone from the perspective of its structural organization. Several prohormones, such as pro-thyrotropin-releasing hormone and pro-gonadotropin-releasing hormone, have structured prodomains, whereas the active hormone domain(s) are completely disordered (31). In contrast, proglucagon exhibits disordered prodomains (GRPP, IP-1, and IP-2), with mostly ordered hormone domains, as our previous work has shown (33).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Proglucagon is a unique prohormone from the perspective of its structural organization. Several prohormones, such as pro-thyrotropin-releasing hormone and pro-gonadotropin-releasing hormone, have structured prodomains, whereas the active hormone domain(s) are completely disordered (31). In contrast, proglucagon exhibits disordered prodomains (GRPP, IP-1, and IP-2), with mostly ordered hormone domains, as our previous work has shown (33).…”
Section: Discussionmentioning
confidence: 86%
“…Interestingly, unlike other prohormones, the ␣-helices lie within ordered hormone-encoding regions and not in a prodomain (31). Additionally, these hormone domains are evolutionarily conserved, particularly regarding their biophysical characteristics (32).…”
mentioning
confidence: 99%
“…Different from CPP, it delivers peptides to the cell membrane, but does not accompany them into the cytosol (Figure 1f), thus avoiding any intracellular influence of the material on the target cells. More interestingly, PEG-PE micelles can transform peptides from non-α-helix into α-helix, which is favorable for membrane translocation [46]. In fact, several endeavors have been made to stabilize peptides in α-helix for better cytosolic delivery [12–16].…”
Section: Discussionmentioning
confidence: 99%
“…Employing neuropeptide hormones and model substrates we could then show that impaired ER import of intrinsically disordered proteins (IDPs) is a general phenomenon and not a specific feature of PrP mutants. Specifically, these studies revealed that IDPs require alpha-helical domains in addition to the N-terminal signal peptide for efficient Sec61-mediated transport into the ER [16,[18][19][20][21].…”
Section: Prion Protein-induced Neurodegenerationthe Cytoplasmic Connementioning
confidence: 99%